2017
DOI: 10.1242/bio.027847
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of mechanical force required for cell extrusion in zebrafish embryonic epithelia

Abstract: When cells in epithelial sheets are damaged by intrinsic or extrinsic causes, they are eliminated by extrusion from the sheet. Cell extrusion, which is required for maintenance of tissue integrity, is the consequence of contraction of actomyosin rings, as demonstrated by both molecular/cellular biological experimentation and numerical simulation. However, quantitative evaluation of actomyosin contraction has not been performed because of the lack of a suitable direct measurement system. In this study, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…The factor of 12 = 2 × 6 is due to the hexagonal structure of the cell sheet. Note that our estimate of the extrusion energy is consistent with the finding in Yamada et al (2017) for epithelial cell extrusion. Here, an actomyosin ring is measured to exhibit a contraction force of the order of 1kPa, which results in an extrusion energy of the order 1kPa × 3 ≈ 3 × 10 −13 J.…”
Section: Parameter Estimation and Robustnesssupporting
confidence: 89%
See 1 more Smart Citation
“…The factor of 12 = 2 × 6 is due to the hexagonal structure of the cell sheet. Note that our estimate of the extrusion energy is consistent with the finding in Yamada et al (2017) for epithelial cell extrusion. Here, an actomyosin ring is measured to exhibit a contraction force of the order of 1kPa, which results in an extrusion energy of the order 1kPa × 3 ≈ 3 × 10 −13 J.…”
Section: Parameter Estimation and Robustnesssupporting
confidence: 89%
“…In Eskandari & Salcudean (2008), a typical value for the dynamical viscosity µ was reported to be on the order of 250Pa s. This can be related to the coefficient γ by Stokes' Law of viscous drag, γ = 6πµ . We now compare our model with epithelial cell extrusion and use the typical cell speed reported in Yamada et al (2017), v 0 ≈ 1mm h −1 and use the typical cell size reported in Brown & Bron (1987), 2 = 13µm. With these numbers, our model predicts a typical extrusion energy on the order of 12V 0 ≈ 12 × 6πµ 2 v 0 ≈ 2 × 10 −13 J.…”
Section: Parameter Estimation and Robustnessmentioning
confidence: 99%
“…The factor of 12 = 2 × 6 is due to the hexagonal structure of the cell sheet. Note, that 272 our estimate of the extrusion energy is consistent with the finding in [41] for epithelial 273 cell extrusion. Here, an actomyosin ring is measured to exhibit a contraction force of the 274 order of 1kPa, which results in an extrusion energy of the order 1kPa × Cell proliferation is simulated as a Poisson process by choosing a rate Γ for each cell 281 to divide in each time unit.…”
supporting
confidence: 83%
“…As a starting point for our model, we consider the model suggested 39 in [20] which was used to study directional adhesion mediated by apical-basal (AB) 40 polarity and PCP. The model in [20], however, could not explicitly account for changes 41 in cell shapes. Here, we show that the effect of cell wedging can be modeled within a 42 point-particle representation by modifying cell-cell forces to favor a tilt in AB polarities.…”
mentioning
confidence: 99%
See 1 more Smart Citation